P041: Accuracy of medical student-performed point-of-care ultrasound in the diagnosis of distal radius fractures in adults. (2nd June 2016) - Farnell, L.; Hall, A.K.; McKaigney, C.
Abstract : Introduction: Previous investigations of the diagnostic accuracy of point-of-care ultrasound (POCUS) in distal radius fractures (DRF) report a wide range of sensitivities (71%-98%) and specificities (73%-100%) when performed by medical professionals, which may reflect inconsistencies in POCUS training or sonographer experience. The purpose of this study was to determine the accuracy of POCUS performed by pre-clerkship medical students with minimal POCUS training compared to standard radiography in diagnosing DRF in adult patients with traumatic wrist injuries, in order to assess POCUS as an alternative to traditional radiographic imaging.Methods: This prospective observational study was conducted from June to September 2015. The study population consisted of adults presenting to the emergency department (ED) with distal forearm pain secondary to traumatic injury within the past seven days and for whom radiographic imaging was ordered. Patients were evaluated using POCUS performed by medical students with no prior experience who had received one hour of POCUS training taught by an emergency ultrasound fellowship-trained ED physician. A pre-test probability of fracture was stratified as low or high and documented independently by the treating physician. Students were blinded to pre-test probability and radiography results.Results: Of the 52 patients enrolled, 18 had DRF diagnosed by radiographic imaging. Compared to radiography, student-performed POCUS had 72% overall sensitivity (95% CI, 47%-90%) and 85% specificity (95% CI, 69%-95%), with 81% overall accuracy. In the high pre-test probability group (N = 20), POCUS had 80% sensitivity (95% CI, 52%-96%) and 60% specificity (95% CI, 15%-95%). In the low pre-test probability group (N = 32), POCUS had 33% sensitivity (95% CI, 1%-91%) and 90% specificity (95% CI, 73%-98%).Conclusion: POCUS performed by medical students demonstrated reasonable success in diagnosing DRF, with overall sensitivity and specificity in keeping with published data. Within the low pre-test probability group, the diagnostic accuracy of POCUS suggests that ultrasound was an unreliable alternative to radiographic imaging for DRF in this cohort. Future analysis of the factors leading to DRF missed by POCUS as being related to adequacy of POCUS training, image capture, or sonographer experience will further explore the utility of POCUS as a diagnostic alternative.